Da Sierra Maestra à Revolução: o olhar do jornal Diário de Notícias (RS) sobre Cuba (1957-1960) - Sabadini, Geanine (2017)
This thesis is the result of a research carried out in the newspaper Diário de Notícias (RS), a representative of the major press, about the news and articles about the Cuban Revolution published between 1957 and 1960. In this four-year time block we analyzed the reception of the Cuban revolutionary process and the image that this newspaper spread about Cuba in Brazil. We also considered the production of books and articles by intellectuals who dealt with the theme of the Cuban Revolution, the press, Cuba's relations with Brazil and Latin America, the influence exerted by the Cuban process in the Brazilian and international political struggle, and the revolutionary leaders, such as Fidel Castro and Ernesto "Che" Guevara, among other topics addressed throughout the years in which the journal highlighted this process. The objective of this research is to analyze the contents of the Diário de Notícias newspaper about the Cuban Revolution, in order to know the representations and interpretations that this newspaper provided to the Brazilians, as well as the image that the newspaper traced of the Caribbean island and the controversies that were raised. In this sense, this study also seeks to identify the processes of construction of the images and affirmations referring to the Cuban Revolution, with the subsequent establishment of positions on the theme; to analyze the motivations of these positions and descriptions, to characterize the ideologies present in the newspaper's discourses, to understand the debates generated in the Brazilian soil about the episodes lived in Cuba and to interpret the possible repercussions of those events in Brazilian society and culture. Therefore, we analyze some methodological aspects combined with results of research in the press. More than making a comparative history, we seek a connective history that goes beyond causal and effect elements and that works with several worlds: the soviet socialist, the american capitalist, and the latin american. We make a brief history about the newspaper Diário de Notícias and, at the end of the paper, we analyze the representations of the journal on different aspects of the revolutionary process, and how they contributed to the construction of the image of the revolution in Brazilian public opinion.